Design and modelling of silicon MEMS accelerometer - Hrairi, Meftah; Baharom, Badrul Hanafi (Inderscience Publishers, 2013)
In developing micro electro mechanical systems (MEMS), finite element analysis (FEA) is usually relied upon to study these micro-structures in determining stress, deformation, resonance, temperature distribution, electromagnetic interference, and electrical properties. With this kind of approach, the performance of the devices can be easily expanded, as well as reducing the time and cost of MEMS production. This paper focuses on the modelling of silicon MEMS accelerometer in an attempt to design a surface micro-machined accelerometer that satisfies certain pre-determined specifications.